Turnover e aninhamento de hifomicetos aquáticos em riachos subtropicais de diferentes usos da terra. - Rasvailer, Vinícius da Silva (2024)
Streams, small rivers, are endowed with exclusive energetic dynamics: decomposition of allochthonous material, and formation of microhabitats and ecotones between aquatic communities and riparian vegetation. Regarding this input of organic matter, aquatic fungi make up most of the biomass of organic matter decomposers, they are biomineralizers of foliar nutrients and through decomposition link the matter to the entire trophic network. Aquatic fungi are a polyphyletic group adapted to this environment, and have different taxonomic levels grouped together. These microorganisms are the target of ecological studies due to their important, still their spatial distribution still lacks elucidation, as well as the influence of limnological on biotic parameters. The fungal communities, composition and beta diversity, were investigated in this study separated into two approaches: i) the beta diversity of aquatic fungi in streams under different land uses; ii) the nesting of fungal eDNA sequences in a protected area and an impacted area. The biotic data were obtained from leaf mixes, and represent the biodiversity of the aquatic FUNGA present in streams of the Atlantic Forest, being pioneering studies for the subtropical region. Furthermore, the results may contribute as a basis for future studies within the mycology of aquatic environments. Approach I, in a taxonomic approach, demonstrated fungal diversity in presence of ambiental heterogeneity. Approach II, through metabarcoding, demonstrates the sensitivity of the use of genomic databases in ecological analyses. The results presented here reinforce the need for management and conservation plans for riparian vegetation, which forms the aquatic microecosystem, used by fungi for their decomposition and other ecosystem functions.